To Develop a Quality Additional School Curriculum on Kratip Khao Weaving for Pathomsuksa 5 - แก้วมณีชัย, ลิขสิทธิ์ (RMUTI Journal Humanities and Social Sciences, 2015)
The purposes of this study were (1) To develop a quality additional school curriculum on Kratip Khao weaving for pathomsuksa 5 (2) To find out an efficiency of the lesson plans for the additional school curriculum with a required criterion of 85/85 (3) To find out the effectiveness index of the developed lesson plans (4) To compared learning achievement with the additional school curriculum (5) To find out the satisfaction of the Pathomsuksa 5 students with the learning activities of the additional school. The sample were 22 students in the first semester in the 2013. The discrimination index was 0.45 to 0.82 and reliability was 0.90. Statistics used for data analysis were mean standard deviation, and Dependent Samples t - test. The results of the study were as follows : (1) The quality of lesson plans for the curriculum was also judged to be at the very good level. (2) The efficiency of the lesson plans for the additional school curriculum was at 84.25/83.48, which was higher than the established requirement of 85/85 (3) The effectiveness index of lesson plans was 0.6202 (4) The lesson plans had higher learning achievement after learning than befor learning at the 0.01 level of significance (5) The students’ satisfaction on Kratip Khao, was at a good. ( = 3.68)